2016
DOI: 10.1103/physrevlett.116.125301
|View full text |Cite
|
Sign up to set email alerts
|

Schrieffer-Wolff Transformation for Periodically Driven Systems: Strongly Correlated Systems with Artificial Gauge Fields

Abstract: We generalize the Schrieffer-Wolff transformation to periodically driven systems using Floquet theory. The method is applied to the periodically driven, strongly interacting Fermi-Hubbard model, for which we identify two regimes resulting in different effective low-energy Hamiltonians. In the nonresonant regime, we realize an interacting spin model coupled to a static gauge field with a nonzero flux per plaquette. In the resonant regime, where the Hubbard interaction is a multiple of the driving frequency, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
207
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(220 citation statements)
references
References 89 publications
5
207
2
Order By: Relevance
“…In the strongly interacting regime, the driving can induce the formation and dissociation of doublons. These processes involve the absorption and emission of photons with a probability amplitude proportional to J l (2Eδ/ω) [33]. Thus, for small driving amplitudes, 2Eδ < ωl = U (where δ is the distance between neighboring sites and l is the order of resonance), the probability is very small, and doublons persist in time.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In the strongly interacting regime, the driving can induce the formation and dissociation of doublons. These processes involve the absorption and emission of photons with a probability amplitude proportional to J l (2Eδ/ω) [33]. Thus, for small driving amplitudes, 2Eδ < ωl = U (where δ is the distance between neighboring sites and l is the order of resonance), the probability is very small, and doublons persist in time.…”
Section: Modelmentioning
confidence: 99%
“…A different effective Hamiltonian is obtained depending on whether the system is in the strongly interacting regime (U ω > J ) or the high-frequency regime (ω U > J ). In the first case it corresponds to first performing the SWT and then a hopping renormalization, whereas in the second it is the other way around [32,33]. In the strongly interacting regime, the driving can induce the formation and dissociation of doublons.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained can be interpreted as in Ref. [42]. In fact, in the regime U, ω J, one can see that in a rotating frame defined by the canonical transformation V (t) = e −i(f (t) j jnj +U t j n ↑,j n ↓,j ) , the electron-electron interation U induces non-trivial phase shifts in the hopping amplitude.…”
Section: Numerical Resultsmentioning
confidence: 81%
“…The effects of interactions between electrons in periodically driven systems have received much attention in recent times [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] . It has been shown that a sinusoidal perturbation of the Hubbard model can lead to coherent destruction of tunneling, creation of gauge fields, and density-dependent tunneling 64 .…”
Section: Introductionmentioning
confidence: 99%